Efficiency Measurement of Maintenance Costs on Customer Service Process PT Indonesia Comnets Plus West Java - Ika Rizky Setyaningrum; Palti Marulitua Sitorus (Faculty of Economics and Business, University of Pasundan, 2015)
Information technology is growing rapidly. The problems arising in the conjunction magnitude of information technology devices are how to manage, maintain, and calculate the amount of required investments. The purposes of this study are to measurepreventive and corrective cost optimization maintenance which determines the most optimal performance for alternative maintenance activity. The case studies in this research is PT Indonesia Comnets Plus (ICON +) West Java focusing on how the process of customer service telecommunication maintenance. Analysis techniques used are descriptive and optimization analysis. The level of corrective maintenance costs are known through services damage probability, average cost of service damage in the period of 2011-2014, and corrective cost analysis formula. To determine the level of preventive maintenance costs, it requires the calculation of damage probability screened estimated monthly service and then calculating the total cost of preventive maintenance. The analysis requires amount of damage and cost of protecting canceling services. The result, general implementation of maintenance services has been running well, but not optimal. Period of preventive maintenance services can be optimized with an average of 12-month treatment.